2017
DOI: 10.1016/j.cotox.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of the AhR structure and interactions can shed light on ligand-dependent activation and transformation mechanisms

Abstract: Molecular modeling has given important contributions to elucidation of the main stages in the AhR signal transduction pathway. Despite the lack of experimentally determined structures of the AhR functional domains, information derived from homologous systems has been exploited for modeling their structure and interactions. Homology models of the AhR PASB domain have provided information on the binding cavity and contributed to elucidate species-specific differences in ligand binding. Molecular Docking simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…17 Therefore, the use of computational modeling is essential for the molecular understanding of the AhR structure and interactions. 18 …”
Section: Introductionmentioning
confidence: 99%
“…17 Therefore, the use of computational modeling is essential for the molecular understanding of the AhR structure and interactions. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we found no changes in transcription before or during the first three months of our experiment. However, once animals emerged from winter dormancy the following spring (222 days post experiment), we found that exposed and infected (diseased) tortoises had decreased transcription for four genes responding to defenses against microbial pathogens (Mx1, Kibenge et al, ; ATF; Zhou et al, ), cellular and oxidative stress (SOD; Walsh et al, ; Sarma & Sharma, ), and cell differentiation, growth, and renewal as well as ligand proliferation and activation of protein chaperones (AHR; Stanford et al, 2016; Bonati et al, ). General patterns of downregulated transcript profiles have been previously observed in adult tortoises characterized as diseased and ill (Drake et al, ) and juvenile tortoises malnourished from invasive plant diets (Drake et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A domino effect of molecular signaling and pathway interruption may impede reactions from reaching their desired target. For example, AHR is well known to respond to a diversity of ligands with the induction of expression of many genes and production of different biological and toxic effects (Bonati, Corrada, Tagliabue, & Motta, 2017;Schmidt & Bradfield, 1996). AHR also plays key regulatory roles in a variety of endogenous developmental and immune response processes (Esser & Rannug, 2015) that can affect the binding and activation of targeted proteins such as heat shock proteins.…”
Section: Pathogen and Host Dynamics In Immunomodulationmentioning
confidence: 99%
“…While the exact mechanism(s) by which TCDD and IR bind to and activate the AhR remain to be elucidated, the results presented here demonstrate that the differential interactions of these ligands with residues within the LBD of the hAhR are responsible for the enhanced signaling potency of IR. One avenue in which to gain additional insights into similarities and differences in the interaction of TCDD and IR with residues inside the binding cavities of the hAhR and mAhR is by performing molecular docking of these ligands into the homology models of their LBDs [ 45 ]. Docking analysis of TCDD within both the AhR LBDs has been previously reported by our laboratory [ 35 ], and the docking simulations of IR binding presented here have allowed prediction of the binding geometries and direct comparison with those of TCDD.…”
Section: Discussionmentioning
confidence: 99%